Automated Filling Equipment Allows Increase in the Maximum Dose to Be Filled in the Cyclops® High Dose Dry Powder Inhalation Device While Maintaining Dispersibility - Imco Sibum; Paul Hagedoorn; Carel O. Botterman; Henderik W. Frijlink; Floris Grasmeijer (MDPI AG, 2020)
In recent years there has been increasing interest in the pulmonary delivery of high dose dry powder drugs, such as antibiotics. Drugs in this class need to be dosed in doses far over 2.5 mg, and the use of excipients should therefore be minimized. To our knowledge, the effect of the automatic filling of high dose drug formulations on the maximum dose that can be filled in powder inhalers, and on the dispersion behavior of the powder, have not been described so far. In this study, we aimed to investigate these effects after filling with an Omnidose, a vacuum drum filler. Furthermore, the precision and accuracy of the filling process were investigated. Two formulations were used-an isoniazid formulation we reported previously and an amikacin formulation. Both formulations could be precisely and accurately dosed in a vacuum pressure range of 200 to 600 mbar. No change in dispersion was seen after automatic filling. Retention was decreased, with an optimum vacuum pressure range found from 400 to 600 mbar. The nominal dose for amikacin was 57 mg, which resulted in a fine particle dose of 47.26 ± 1.72 mg. The nominal dose for isoniazid could be increased to 150 mg, resulting in a fine particle dose of 107.35 ± 13.52 mg. These findings may contribute to the understanding of the upscaling of high dose dry powder inhalation products.